2008
DOI: 10.1074/mcp.m700305-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Serum Levels of Tissue Inhibitor of Metalloproteinases-1 Are Associated with Prognosis in Node-negative Breast Cancer

Abstract: The tumor level of TIMP-1 has been suggested as a new prognostic marker in breast cancer. The purpose of this study was to investigate whether TIMP-1 also carries prognostic information when measured in blood as this is a much more preferable material compared with tumor extracts. Using ELISA, TIMP-1 was measured in prospectively collected preoperative plasma and serum samples from 519 patients with primary breast cancer, and the measurements were related to patient outcome. The median age of the patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…As a final remark, it should be mentioned, as emphasized in the introduction, that a number of previous studies have demonstrated that tumor tissue levels of TIMP-1 as well as TIMP-1 measured in blood carry prognostic information in primary breast cancer [7][8][9][10][11]. It is important to be aware of the various limitations in prognostic studies where endpoints such as recurrencefree survival and overall survival are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a final remark, it should be mentioned, as emphasized in the introduction, that a number of previous studies have demonstrated that tumor tissue levels of TIMP-1 as well as TIMP-1 measured in blood carry prognostic information in primary breast cancer [7][8][9][10][11]. It is important to be aware of the various limitations in prognostic studies where endpoints such as recurrencefree survival and overall survival are used.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue inhibitor of metalloproteinases-1 (TIMP-1) has proven to be a promising marker in breast cancer carrying both prognostic [7][8][9][10][11] and, as shown more recently, predictive information [12][13][14][15]. For example, our laboratory has previously demonstrated that high primary tumor tissue levels of TIMP-1 were significantly associated with a poor response to the most frequently used chemotherapeutic drugs in metastatic breast cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…High serum VEGF-165 (the predominant isoform of VEGF-A in circulation) levels have also been associated with tumor stage, tumor grade, and poor prognosis in RCC (30). Elevated levels of tumor and/or plasma TIMP-1 are associated with poor survival prognosis in a number of tumor types [colorectal (31,32), gastric (33), breast (34)(35)(36), ovarian (37), and lung (38) cancers]. In a number of these studies, plasma TIMP-1 was an independent prognostic factor upon multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects are likely mediated by their direct binding to cell-surface receptors and subsequent signaling activation, including the mitogen-activated protein kinase and the cyclic adenosine 3',5'-monophosphate-protein kinase A (PKA) pathways (14,15). TIMP1 has been extensively studied in recent years as a promising prognostic marker in colorectal, endometrial and breast cancer (16)(17)(18)(19)(20)(21)(22). Recently, Spindler et al showed that TIMP1 has a potential role as a prognostic biomarker in patients with metastatic colorectal cancer treated with cetuximab and irinotecan.…”
mentioning
confidence: 99%